(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Supply chain and logistics optimization has become increasingly important as India’s e-commerce sector grows rapidly. To meet growing customer expectations of speed and reliability, e-commerce companies are turning to technology-driven solutions including AI-enabled route optimisation, machine learning for demand forecasting and real-time tracking. The focus of this project is to analyse the challenge, which are faced by e-Kart, Delhivery or other companies regarding logistics and supply chain operations. It is expected that through the research on operational performance, technology, and customer satisfaction, the companies will be able to solve logistical issues like poor infrastructure, disturbances from external parties, high operating costs, etc. Through quantitative and qualitative data, the study will determine how technology and sustainable practices can be implemented to enhance supply chain performance in India’s e-commerce landscape. We will use various statistical methods like regression, anova, and factor analysis to pinpoint which logistics problems, which consumer satisfaction, and which tech integration issues matter most. The proposed study intends to develop an integrated framework linking technology adoption- operation performance- and sustainability which the e-commerce firms can utilize to improve operations. The expected results are that technology solutions increased efficiency and decreased costs while maximizing customer satisfaction. But it is estimated that the constraints on infrastructure, the scalability of green logistics, and external disruption will be large hindrances to further optimization. This study will add to the literature gap by assessing the scalability of sustainable logistics practices with technological advancement. Further, it will provide recommendations for company executives who want to optimize the supply chain and logistics functions in India.